Homicide through the perspective of investigation and psychological profiling – a case study (Academic Journal of Internal Affairs, 2021)
Though by definition profiling is a psychological activity, nowadays statistical approaches and models based on scientific research is the trend in profiling. This process is understandable but it is increasingly clearer as well that excluding the psychological method from profiling reduces its depth, richness and thus usability. Psychological profiles are more complex, richer and expand the possible areas of applications of profiling.  We also reflect on the criticism directed at the method and its validity. In our study we present the method of psychological profiling through a double homicide committed on 16 November 2004 and solved in the meantime. We present the structured process of psychological profiling, its successive stages and apply these stages to the crime committed and described in detail. Finally, the profile is compared with the offender’s data. The profile, which was compiled by the psychologist on the basis of the known details of the crime, without knowing the perpetrator, shows a high degree of similarity with the perpetrator who was later identified. At the same time, even the best profile can only help the investigation if it is used in a meaningful way. We hope to contribute to dispelling the mystique and misconceptions surrounding the method of psychological profiling, in order to give investigators a better understanding how it can be and cannot be used for. In doing so, we aim to enrich the applicable investigative tools and to improve the undeservedly neglected status of profiling at the same time.
Keywords: criminal profiling; criminal psychology; homicide; forensics